Analisis Sumber Daya Manusia Dalam Meningkatkan Kinerja Pegawai Dengan Metode Qspm Pada Kelurahan Lengkong Gudang Timur Di Kota Tangerang Selatan - Dedek Kumara; Suci Fitri Ramadhani (Peneliti.net, 2023)
Human resources have an effect on improving the performance of an organization's employees so that it is necessary to improve the quality of good employee performance, through formal education channels and the need for educational training activities for self-development. From the results of observations that researchers conducted in Lengkong Gudang Timur sub-district, South Tangerang, said that employees in an agency in carrying out state duties were very much asked to be ready and alert in carrying out their duties and ready to provide good service to the community. If employees of an agency provide poor service quality, the community will also get a poor level of satisfaction, even the community feels disadvantaged because they may have been waiting in line for a long time and so on, and vice versa if employees can serve the community well, the level of community satisfaction will be high and the community will feel happy doing administration at the agency or at the office of the government agency. The type of research used in this research is qualitative research. Qualitative research is generally descriptive in nature. The instrument used is through observation and interviews. Observations made by researchers include any focus of the studies studied. The purpose of this study was to determine the performance of village employee resources in Lengkong Gudang Timur, South Tangerang City. The limitation of the problem in this study focuses on the work of Lengkong Gudang Timur sub-district employees using the ifas and efas methods. Then the urgency of this research is useful for related parties as an additional reference, included in making regulations and providing recommendations in terms of developing related policies in improving employee performance. This research is a competitive research with Beginner Lecturer Research (PDP) scheme. The expected output of this research is publication in the form of an accredited national scientific journal.